Using a baculovirus display library to identify MHC class I mimotopes - Wang, Yibing (National Academy of Sciences, 2005)
We have developed a baculovirus-based display system for identifying antigen mimotopes for MHC class I-specific T cells. The mouse MHC class I molecule, D(d), was displayed on baculovirus-infected insect cells with a library of 9- and 10-mer peptides tethered via a flexible linker to the N terminus of β2 microglobulin. As a test case, the library was screened by flow cytometry by using a multimeric fluorescent αβTCR from a mouse T cell specific for D(d) plus an unknown self peptide. A mimotope was identified that, when bound to D(d), stimulated the T cell to secret IL-2. The sequence of the mimotope was used to identify a self peptide present in a mouse protein, Spin. The Spin peptide, when complexed with D(d), also activated the T cell. This technique should be generally useful in identifying and manipulating MHC class I peptide mimotopes and epitopes.